The little book of leadership development 50 ways to bring out the leader in every employee - Allen, Scott J. 1972-; Kusy, Mitchell (American Management Association, 2011)
Focuses on what really works to get people motivated, working effectively, and acting as leaders themselves. This book delivers streamlined instructions on modeling behaviors, sharing information, building accountability, stretching teams, providing feedback, and 45 other practical strategies.